Sarcoma Immunotherapy: Past Approaches and Future Directions. (20th March 2014) - D'Angelo, S. P.; Tap, W. D.; Schwartz, G. K.; Carvajal, R. D.
Abstract : Sarcomas are heterogeneous malignant tumors of mesenchymal origin characterized by more than 100 distinct subtypes. Unfortunately, 25–50% of patients treated with initial curative intent will develop metastatic disease. In the metastatic setting, chemotherapy rarely leads to complete and durable responses; therefore, there is a dire need for more effective therapies. Exploring immunotherapeutic strategies may be warranted. In the past, agents that stimulate the immune system such as interferon and interleukin-2 have been explored and there has been evidence of some clinical activity in selected patients. In addition, many cancer vaccines have been explored with suggestion of benefit in some patients. Building on the advancements made in other solid tumors as well as a better understanding of cancer immunology provides hope for the development of new and exciting therapies in the treatment of sarcoma. There remains promise with immunologic checkpoint blockade antibodies. Further, building on the success of autologous cell transfer in hematologic malignancies, designing chimeric antigen receptors that target antigens that are over-expressed in sarcoma provides a great deal of optimism. Exploring these avenues has the potential to make immunotherapy a real therapeutic option in this orphan disease.